2012
DOI: 10.1016/j.ibmb.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional fat body proteomics and gene targeting reveal in vivo functions of Drosophila melanogaster α-Esterase-7

Abstract: Carboxylesterases constitute a large enzyme family in insects, which is involved in diverse functions such as xenobiotic detoxification, lipid metabolism and reproduction. Phylogenetically, many insect carboxylesterases are represented by multienzyme clades, which are encoded by evolutionarily ancient gene clusters such as the α-Esterase cluster. Much in contrast to the vital importance attributed to carboxylesterases in general, the in vivo function of individual α-Esterase genes is largely unknown. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…Although the physiological substrates of insect α-CBEs are unknown, recent MS results have shown that D. melanogaster αE7 is expressed in the fat body lipid droplet proteome (11), implying a role in lipid or cholesterol metabolism. This work has been extended to show that D. melanogaster αE7-null mutants exhibit reduced lifespan, lowered insecticide tolerance, and reduced lipid storage capacity (6).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although the physiological substrates of insect α-CBEs are unknown, recent MS results have shown that D. melanogaster αE7 is expressed in the fat body lipid droplet proteome (11), implying a role in lipid or cholesterol metabolism. This work has been extended to show that D. melanogaster αE7-null mutants exhibit reduced lifespan, lowered insecticide tolerance, and reduced lipid storage capacity (6).…”
mentioning
confidence: 99%
“…However, α-CBEs, such as αE7 in L. cuprina (LcαE7), confer a significant protective effect on insects owing to their ability to bind and slowly hydrolyze OPs (6). It has also been shown that this CBE-mediated OP resistance can be increased through G137D and W251L point mutations (4, 7).Insect α-CBEs, including LcαE7, are thought to play important physiological roles in lipid and xenobiotic metabolism (6,8). They are one of the most abundant protein families in insects, with between 20 and 40 active CBEs predicted to be expressed by the fruit fly Drosphila melanogaster (9, 10).…”
mentioning
confidence: 99%
See 3 more Smart Citations